REVIEW (ARTICLE) ON THE ROLE OF FUNGI IN THE BIODEGRADATION OF SOIL CONTAMINATED WITH HEAVY METALS - Duha Bahaa Mohammed Al Fayaad (European Science Publishing, 2024)
Several biodegradation techniques harness a diverse array of microorganisms to remediate contaminated environments. Over the past 15 years, biodegradation has emerged as a powerful tool for environmental cleanup. The extracellular enzymes of algae, bacteria, yeast, and fungi can be harnessed to accelerate the biodegradation process. Fungi, in particular, have shown remarkable adaptability to a variety of pollutants and possess the unique ability to bioabsorb and bioconvert these pollutants into less harmful substances. This inherent potential of fungi in decontaminating polluted environments instills a sense of hope for the future of environmental cleanup.
Keywords: fungi, biodegradation, metals.